Pembabakan Kebijakan Lingkungan Hidup Nasional Berbasis Kearifan Lokal sebagai Strategi Adaptasi Menghadapi Perubahan Iklim - Sapto Hermawan (Faculty of Law, Universitas Wijayakusuma, 2019)
national policies that the government intends to implement by basing on the interests of indigenous peoples as vulnerable groups related to adaptation to climate change. Through the use of normative studies, an explanation can be given that the abolition of domestic policy based on local wisdom as an adaptation strategy in dealing with climate change can be taken through five stages, namely (1) observation phase, (2) assessment stage, (3) planning stage, (4) the implementation phase, and (5) the monitoring and evaluation stage.Keywords: environmental policy, local wisdom, climate change